Dryland cereals and Household Food Security in Tanzania: Potential and Constraints of Improved Sorghum Cultivars - Schipmann-Schwarze, C.; Muange, Elijah; Orr, Alastair; Mafuru, January M. (My University, 2011)
More than one third of the population in Africa is still facing undernourishment and malnutrition. While poor and food-insecure people are most often living in unfavourable agricultural zones, such as semi-arid areas, only few studies have assessed the potential of well adapted dryland cereals to contribute to local food security. Here, we analyze the case of sorghum in Tanzania, and particularly focus on the role of improved sorghum cultivars. Using survey data from smallholder farmers and econometric techniques, we show that sorghum contributes to the food supply of a household. Despite the promise of higher yields and better resistance of improved sorghum cultivars to some biotic and abiotic stresses, adoption rates are, however, still low. Our results indicate that access to information and diversified networks constitute serious adoption constraints. National extension systems are a major bottleneck in overcoming such constraints.